Plant isoflavones can prevent adverse effects of benzene on porcine ovarian activity: an in vitro study - Sirotkin, Alexander; Záhoranska, Zuzana; Tarko, Adam; Popovska-Percinic, Florina; Alwasel, Saleh; Harrath, Abdel Halim (Springer Science and Business Media LLC, 2020)
We evaluated the influence of the oil-related environmental contaminant benzene (0, 10, 100, or 1000 ng/mL) alone and in combination with apigenin, daidzein, or rutin (10 μg/mL each) on viability; proliferation (accumulation of proliferating cell nuclear antigen); apoptosis (accumulation of Bax); and release of progesterone (P), testosterone (T), and estradiol (E) in cultured porcine ovarian granulosa cells. Cell viability; proliferation; apoptosis; and release of P, T, and E have been analyzed by the trypan blue test, quantitative immunocytochemistry, and ELISA, respectively. Benzene did not affect apoptosis, but reduced ovarian cell viability and P and E release, and promoted proliferation and T output. Apigenin did not affect cell viability, but stimulated proliferation and T and E release, and inhibited apoptosis and P secretion. It prevented and reversed the action of benzene on proliferation and P and T release, and induced the inhibitory action of benzene on apoptosis. Daidzein promoted cell viability, proliferation, P release, but not apoptosis and T or E release. Daidzein induced the stimulatory effect of benzene on T, without modifying other effects. Rutin administered alone reduced cell viability and apoptosis, and promoted cell proliferation. Furthermore, rutin prevented and reversed the effect of benzene on proliferation and P and E release. These observations suggest the direct action of benzene and plant polyphenols on basic ovarian cell functions, and the ability of apigenin and rutin, but not of daidzein, to prevent benzene effects on the ovary.
Keywords: Benzene, Apigenin, Daidzein, Rutin, Ovarian cells, Viability, Hormone, Porcine